Teacher Perception on Leaderships: Survey on Public High Schools in Bandung Regency - Vicky Achmad Zulfikar; Robbi Saepul Rahman; Nita Yura Roslina (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2021)
The leadership role of the principal is one aspect in improving the quality of education. Principal leadership consists of various components, namely leadership styles, educators, managers, administrators, supervisors, leaders, innovators and motivators. This study aims to validate the components proposed in this study whether they are the forming factors of the principal's leadership variable. To answer the research questions, the researchers used a quantitative approach with factor analysis techniques to validate the predetermined components perceived by the teacher. Respondents are high school teachers at one of the secondary schools in Bandung Regency as many as 75 teachers. The results indicate that it is evident that the principal's leadership consists of 8 components, namely leadership style, educator, manager, administrator, supervisor, leader, innovator and motivator. The results of the study indicate that the principal's measurement can use the 8 factors that make up the principal's leadership variable.